Influence of shot peening on the mechanical properties of bulk amorphous Vitreloy 105*. (2nd September 2017) - Grell, Daniel; Gibmeier, Jens; Dietrich, Stefan; Silze, Frank; Böhme, Luisa; Schulze, Volker; Kühn, Uta; Kerscher, Eberhard
ABSTRACT: The quasi-static and cyclic properties of bulk glassy Zr52.5 Cu17.9 Al10 Ni14.6 Ti5 alloy (Vitreloy 105) were investigated under three-point bending conditions for two different shot-peened surface states. Residual stress analysis and nanoindentation measurements revealed the presence of compressive residual stresses and an enhanced hardness in the near surface layer after shot peening. Further investigations of the longitudinal cross-sections of the mechanically tested specimens by optical and scanning electron microscopy showed small cracks propagating along shear bands in the vicinity of the fracture surface. The results are in accordance with the improved plasticity of the shot-peened states under quasi-static loading conditions compared to the as-cast reference state. All mechanical testing was carried out with the aim to find a material's state with improved mechanical properties with a special focus on the improvement of the fatigue lifetime and the endurance limit of Vitreloy 105 bulk metallic glass.